Gender, intoxication and the developing brain: Problematisations of drinking among young adults in Australian alcohol policy - Manton, E.; Moore, David (Elsevier BV, 2016)
In this article, we draw on recent scholarly work in the poststructuralist analysis of policy to consider how policy itself functions as a key site in the constitution of alcohol ‘problems’, and the political implications of these problematisations. We do this by examining Australian alcohol policy as it relates to young adults (18–24 years old). Our critical analysis focuses on three national alcohol policies (1990, 2001 and 2006) and two Victorian state alcohol policies (2008 and 2013), which together span a 25-year period. We argue that Australian alcohol policies have conspicuously ignored young adult men, despite their ongoing over-representation in the statistical ‘evidence base’ on alcohol-related harm, while increasingly problematising alcohol consumption amongst other population subgroups. We also identify the development of a new problem representation in Australian alcohol policy, that of ‘intoxication’ as the leading cause of alcohol-related harm and rising hospital admissions, and argue that changes in the classification and diagnosis of intoxication may have contributed to its prioritisation and problematisation in alcohol policy at the expense of other forms of harm. Finally, we draw attention to how preliminary and inconclusive research on the purported association between binge drinking and brain development in those under 25 years old has been mobilised prematurely to support calls to increase the legal purchasing age from 18 to 21 years. Our critical analysis of the treatment of these three issues – gender, intoxication, and brain development – is intended to highlight the ways in which policy functions as a key site in the constitution of alcohol ‘problems’.